Clinical Profile, Complications and Outcomes of Measles among Children: An Observational Study from a Tertiary Care Hospital, South Gujarat, India - Kirti Premabhai Mehta; Ashruti Mahesh Patel; Ankur Patel (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Measles is re-emerging as an infectious disease in children and hence the prevalence has been increasing worldwide. According to the World Health Organisation (WHO), in the year 2018, more than 140,000 deaths occurred globally due to measles and its complications; most common in children <5 years of age. Aim: To evaluate the clinical profile of measles and its complications leading to death in children for better immunisation coverage and prevention of the disease. Materials and Methods: This was a prospective, observational study carried out in the Department of Paediatrics, New Civil Hospital (tertiary care hospital), Surat, Gujarat, India. Patient data was collected from January 2021 to December 2021 and data was analysed from January 2022 to June 2022. Study was done on all children with history of fever with rash and laboratory confirmed positive patients for measles Immunoglobulin M (IgM) antibody titer. Statistical analysis was performed using Statistical Package for the Social Sciences (SPSS) software version 27.0. Results: During the study period only, 42 children with fever and rash had laboratory confirmed measles IgM positive antibody titre. Out of total, 42.86% of the study participants belonged to 1-4 years age group and 50% were unvaccinated. Males were more affected than female. Majority (81%) of cases occurred during late winter and spring seasons and most (78.57%) of the patients belonged to urban slum areas. Most common presenting complaint observed was maculopapular rash in all the children. Majority (95.24%) of the children were in eruptive stage of the disease. A total of 31 patients out of 42 developed complications with pneumonia as most common 38.71% children. All the patients recovered completely and were discharged from the hospital. Conclusion: There was decreasing trend of measles in young children. It can be due to recent immunisation campaigns and better coverage. Half of the patients in study were unvaccinated which indicates, there’s still work left to be done to immunisation scheme for better coverage.